2022
DOI: 10.3390/polym14122426
|View full text |Cite
|
Sign up to set email alerts
|

Control of Stimuli Sensitivity in pH-Switchable LCST/UCST-Type Thermosensitive Dendrimers by Changing the Dendrimer Structure

Abstract: Stimuli-sensitive materials, such as pH- and temperature-responsive polymers, are useful as smart materials. Phenylalanine (Phe)-modified polyamidoamine (PAMAM) dendrimers with succinic acid termini, PAMAM-Phe-Suc, have been reported as unique pH-switchable lower critical solution temperature (LCST)-/upper critical solution temperature (UCST)-type thermosensitive polymers. Regulating the phase transition behavior of dendrimers is important for their applications. This study investigated the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…However, the pH sensitivity tended to decrease with decreasing bound numbers of Phe. Our previous report indicated that the stimuli sensitivity broadened with decreasing bound numbers of Phe in the dendrimer [ 31 ], which is consistent with this result. Thus, our results indicate that the bound number of Phe in the dendrimer is involved not only in the T cell-association property but also in the expression of pH responsiveness.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…However, the pH sensitivity tended to decrease with decreasing bound numbers of Phe. Our previous report indicated that the stimuli sensitivity broadened with decreasing bound numbers of Phe in the dendrimer [ 31 ], which is consistent with this result. Thus, our results indicate that the bound number of Phe in the dendrimer is involved not only in the T cell-association property but also in the expression of pH responsiveness.…”
Section: Resultssupporting
confidence: 89%
“…In this study, CHex- and Phe-modified dendrimers with different bound numbers of Phe were used to investigate the influence of the dendrimer terminal Phe density on cell association and drug delivery ability. Two types of CHex- and Phe-modified dendrimers, PAMAM-CHex-Phe and PAMAM-Phe-CHex, were synthesized by varying the reaction order of cis -1,2-cyclohexanedicarboxylic anhydride and Phe, as shown in Figure 2 [ 30 , 31 ]. In the synthesis of PAMAM-CHex-Phe, the PAMAM G4 dendrimer was reacted with an excess of cis -1,2-cyclohexanedicarboxylic anhydride, followed by a reaction with Phe-OBzl·Tos and the subsequent deprotection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase transitions in solutions of thermosensitive polymers have been studied for a long time [ 1 , 2 , 3 , 4 ]. This issue is not only of academic [ 3 , 5 , 6 , 7 , 8 , 9 ], but also of direct applied interest.…”
Section: Introductionmentioning
confidence: 99%